Evaluation of incorporated phosphorus fertilizer recommendations on no‐till managed winter wheat. Issue 2 (27th October 2021) - Reed, Vaughn; Watkins, Patrick; Souza, Joao; Arnall, Brian
Abstract: The current Oklahoma State University Soil, Water, and Forage Analytical Laboratory (OSU) phosphorus (P) recommendations were developed for conventional tillage systems with P fertilizer incorporated in the soil. The rate recommendations were based on a sufficiency approach, and included a pH adjustment factor. Increased adoption of no‐till (NT) management across the region has resulted in more surface application of fertilizer, without concomitant changes in OSU recommendations. In the 2014–2015 and 2015–2016 growing seasons, nine on‐farm trials were conducted in north‐central Oklahoma to evaluate current winter wheat ( Triticum aestivum L.) P recommendations, and grain yield responses to fertilizer in both P‐sufficient and P‐deficient soils, and acidic or non‐acidic conditions. Phosphorus fertilizer was recommended for eight of the nine locations, while responses were recorded at only five of those eight locations. The results indicate that OSU P recommendations, with a soil acidity adjustment factor, did not limit winter wheat grain yields in NT management. In addition, the application of 30 lb acre –1 P2 O5 offset the effects of soil acidity on P uptake regardless of the degree of acidity. Finally, OSU recommended P on some locations where there was no response, suggesting more work is needed to understand crop response dynamics and build recommendations with increased location specificity. Core Ideas: Oklahoma State University P fertilizer recommendations provided adequate P to support optimum yields on most soils evaluated. An additional 30 lb acre −1 P2 O5 offset the effects of soil acidity on P uptake, regardless of the degree of soil acidity. Phosphorus recommendations based on Mehlich‐3 extraction and soil pH did not limit no‐till wheat fields.